Response Analysis Of The Lower Structure Of Girder Bridge With Lead Rubber Bearing (LRB) And High Damping Rubber Bearing (HDRB) Due To Earthquake Excitation - Donald Essen; Siti Sukainah (NAROTAMA UNIVERSITY, Indonesia, 2021)
Seismic isolation is a system to reduce seismic energy acting on the bridge by adding an object so-called base insulator. The purpose of this study is to obtain a comparison of dimension, damping ratio, and the lower structure response designed as a ductile component with High Damping Rubber Bearings (HDRB) and Lead Rubber Bearings (LRB). This study uses CSI BRIDGE 21 computer program. Earthquake forces analysis uses dynamic analysis with response spectra as final evaluation for the performance of lead rubber bearing and high damping rubber bearings and the load characteristics for bridges is following SNI 1725: 2016 and bridge design for earthquake load is following SNI 2833: 2016. The bridge performance is expected to no longer rely merely on the dimensions and stiffness of the pillars in response to earthquake loads, but also on LRB or HDRB as a structural device on bridge support by increasing the effectiveness of pillar stiffness in providing damping energy during an earthquake.